The Potential of Kaledang (Artocarpus lanceifolius Roxb.) Stem Bark Fractions as an In Vitro Sunscreen - Moh. Arya Avrilio Isa; Hamsidar Hasan; Widy Susanti Abdulkadir; Multiani S. Latif; Dizky Ramadani Putri Papeo (Jurnal Fitofarmaka Indonesia, 2025)
Exposure to ultraviolet (UV) radiation is a major factor causing skin damage that can trigger premature aging, inflammation, hyperpigmentation, and even skin cancer, thereby encouraging the development of natural-based sunscreens as safer and more environmentally friendly alternatives. The stem bark of kaledang (Artocarpus lanceifolius Roxb.) contains active compounds such as flavonoids and phenolics, which have potential as UV absorbers as well as antioxidants. This study aims to determine the in vitro sunscreen activity of kaledang stem bark fractions and to identify the concentration that produces the highest Sun Protection Factor (SPF) value. The research employed an experimental design by testing chloroform, ethyl acetate, and methanol fractions at concentrations of 50, 100, and 200 ppm, respectively, using the SPF assay with UV-Vis spectrophotometry.